"GOLDARHES" As a Digitalization Blood Type Test Device Based on Light Sensors. (July 2020) - Liastra, S. M.; Faadhillah, A.; Dinata, M. T. S.; Mahendra, A. D.; Rohmah, L. N. H.; Yuliyanasari, N.
Abstract: According to the data, high death rate among surgery patients was caused by faulty blood typing which were still manually done and high risk in human error. GOLDARHES is a device to determine blood type uses a light sensor with LDR and LED components and an Arduino microcontroller, then it showed the results on LCD. This device has never been used in Indonesian healthcare facilities. The Casing which is environmental friendly material is made of corn husk waste containing cellulose, lignin, and hemicellulose. In addition, the energy power of the device itself uses a charging system so that it can reduce the amount of chemical waste that is difficult to decompose. The Methods of this research is True Experimental using 100 samples of participants. The results obtained will be displayed on the LCD which is processed in less than 10 seconds. The results of this research was faster than manually test, the mean of test period was take 5 seconds and the sensitivity of the tool is 95%. Thus "GOLDARHES" can be used as an effective, accurate, and fast medical device in determining blood type.